Adolescence in the Time of COVID-19 : Evidence from Bangladesh - Baird, Sarah (World Bank, Washington, DC, 2020)
This note examines the effects of COVID-19 and subsequent economic and educational disruptions on adolescent well-being in Bangladesh. The analysis is based on data from 2,095 in-school adolescents aged 10–18 collected pre-COVID-19 (February–March 2020) through a field survey for an ongoing impact evaluation, and a follow-up virtual survey undertaken early in the pandemic (May-June 2020). Findings show large household-level economic impacts associated with increased food insecurity, anxiety, and mental health issues among adolescents. In addition, school closures have decreased adolescents’ access to learning, increased time spent on household chores, and affected future job aspirations. The impacts are particularly large for girls and for adolescents from more vulnerable households. Policy makers need to consider policies that facilitate school return, targeting girls and the most vulnerable. They also need creative school-based programming to address the likely long-run physical and mental health effects of COVID-19 on young people.